1996
DOI: 10.3109/08958379609005425
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exposure to Low-Level Methyl Tertiary-Butyl Ether (MTBE): Human Reactions and Pharmacokinetic Response

Abstract: This two-part investigation assessed the effects of 1-h exposures to methyl tertiary-butyl ether (MTBE) at an ambient concentration of 1.7 ppm on healthy adults. In one part, four subjects participated in a pharmacokinetic study of blood levels of MTBE. Concentration in blood rose 20-fold from baseline to 17 µg/L by the end of exposure and declined to one half that level at 40 min after exposure. In another part, 43 subjects participated in a double-blind study of reactions to exposures to MTBE (1.7 ppm), to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
(23 reference statements)
2
27
2
1
Order By: Relevance
“…Presumably a sufficiently long chamber exposure to MTBE would allow the determination of the residence time for the fourth compartment (adipose tissue). Cain et al 37 and Johanson et al 38 have reported results from similar chamber studies. Cain et al exposed four subjects to 6,129 µg/m 3 MTBE for 1 hour, resulting in blood levels rising on average from about 1,000 to 17,000 ng/L.…”
Section: Discussionsupporting
confidence: 56%
“…Presumably a sufficiently long chamber exposure to MTBE would allow the determination of the residence time for the fourth compartment (adipose tissue). Cain et al 37 and Johanson et al 38 have reported results from similar chamber studies. Cain et al exposed four subjects to 6,129 µg/m 3 MTBE for 1 hour, resulting in blood levels rising on average from about 1,000 to 17,000 ng/L.…”
Section: Discussionsupporting
confidence: 56%
“…The uptake and elimination of MTBE following inhalation exposure under either controlled conditions or occupational settings have been studied Prah et al, 1995;Cain et al, 1996;Lindstrom and Pleil, 1996;Buckley et al, 1997;Saarinen et al, 1998;Nihle Ân et al, 1998a,b, 1999, Amberg et al, 1999 . Alveolar breath measurement is one method adopted to evaluate the pharmacokinetics of MTBE.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the results of experimental studies in humans in controlled MTBE exposure chambers showed no effects on health (133)(134)(135)(136).…”
Section: Renal Tumorsmentioning
confidence: 99%